Estudo metodológico da reação de Prins em ausência de solventes orgânicos e sua aplicação na síntese de substâncias bioativas - Brito Júnior, Gilmar Araújo (2009)
In this work it was done a methodological study on Prins cyclization reaction in the absence of organic solvents. The synthesis of target compounds was possible by using or the catalytic system pTSA.SiO2(gel) initially developed in this project, as shown in Figure I. As a initial proposal of this work, another catalytics systems were developed, this time using non-protonic Lewis acids. The catalytic system FeCl3.SiO2(aerosil) was shown to be the most advantageous among other catalytic systems developed in parallel experiments. The synthesis of target compounds FLOROL ® (6) and CLARYCET ® (8), in absence of organic solvents, was possible by using this catalytic system. The same catalytic system was employed to the preparation of the skeleton of the compound (+/-)- Diospongin A (Figure II). The developed catalytics systems showed to be effective on the catalysis of Prins cyclization reactions involving oxigenate compounds. But these systems had failed when homoallylics amines were employed and so it XII was not possible to obtain the compounds SS20846 A and pipecolic acid, as shown in Figure III.